Active prey mixing as an explanation for polyphagy in predatory arthropods: synergistic dietary effects on egg production despite a behavioural cost. (15th April 2015) - Marques, Renata Vieira; Sarmento, Renato Almeida; Lemos, Felipe; Pedro‐Neto, Marçal; Sabelis, Maurice W.; Venzon, Madelaine; Pallini, Angelo; Janssen, Arne
Summary: Mixing of prey that differ in nutrient content or toxic compounds (dietary mixing) may allow synovigenic predatory arthropods to balance their diet or dilute toxins of different prey items to maximize performance: dietary mixing may therefore explain the prevalence of polyphagy in this functional group. Several predatory arthropods can redress nutritional imbalances in their diet by actively mixing different diets, based on experiments with artificial diets or with prey that were manipulated to contain different nutrients. Evidence is also accumulating that predator species perform better on a mixed diet of several different prey species, but evidence that they actively forage for different prey species is scarce. Thus, evidence that predators actively forage for a mixed diet consisting of natural, non‐manipulated prey to increase their performance is still rare. Here, we investigate whether arthropod predators invest in achieving an optimal diet by active mixing of different prey species or by simply eating what they encounter. Females of two species of plant‐inhabiting predatory mites produced significantly more eggs when feeding on a prey mixture of co‐occurring phytophagous mites than when feeding on either of the two prey species separately. When the two prey species were offered on two separate, connected patches at some distance from each other, predators commuted significantly more between the two patches to obtain a mixed diet and had a significantly increased egg production than predators that were offered a single prey species on two patches. Thus, predators actively commuted between patches to balance their diet. We propose that active dietary mixing can have synergistic effects on predator fitness and has the potential to explain polyphagy in this functional group. Abstract : Lay Summary